Excavations in North Sinai - Hoffmeier, James Karl; Kitchen, Kenneth A. (Tell el-Borg, 2014)
Intro -- Contents -- Preface -- Abbreviations -- Introduction to the Work at Tell el-Borg -- "The Ways of Horus": Reconstructing Egypt's East Frontier Defense Network and the Military Road to Canaan in New Kingdom Times -- The Geological Setting of Tell el-Borg with Implications for Ancient Geography of Northwest Sinai -- Field I and Miscellaneous Inscriptions -- The Fortification Area -- The Ramesside Period Fort -- Results of the Magnetic Survey at Tell el-Borg, North Sinai, March 2006 and 2007 -- A Report on the Ceramics Recovered from Tell El-Borg -- Levantine-Egyptian Interconnections at Tell el-Borg, North Sinai -- The Cypriot Pottery -- Ceramic Miscellanies -- Metal Weapons.